Paternal representations in late adolescence - Sefer, Nihan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
The present study investigated how fathers and mothers are portrayed in late adolescents̕ mental representations in Turkey with a specific focus on paternal representations. Using Blatt, Chevron, Quinlan, Schaffer and Wein̕s (1988) method of Assessing Qualitative and Structural Dimensions of Object Representations, the contentof the representations, the level of ambivalence, the level of articulation, the verbal fluency, and the developmental level in parental representations were assessed inparental narratives of males and females. The effect of an Expanding Self construal on structure and content of parental representations were also explored. Fifty female and 46 male Bogaziçi University undergraduate students participated in the study providing open-ended descriptions of their mothers and fathers. Analyses indicated a significant main effect of parental gender and significant main effect of late adolescent̕s gender in both maternal and paternal descriptions. Overall results suggested that traditional discourses regarding fathers are still dominant in themental worlds of individuals; mothers were described as more affectionate, warmer,stronger, more constructively involved and more nurturant than fathers. Compared to mothers, fathers were described as more ambitious, more intellectual and more successful and they were described with higher levels of ambivalence, verbal fluency and conceptual level. Correlations revealed that as Expanding Self scores increased, both males and females ascribed more negative qualities for their mothers, however inpaternal representations only females represented their fathers more negatively. The results are discussed on the basis of relational and developmental differences within the specific cultural context.
Keywords: Adolescent psychology -- Turkey.